Cancer Statistics, 2006 - Jemal, Ahmedin; Siegel, Rebecca; Ward, Elizabeth; Murray, Taylor; Xu, Jiaquan; Smigal, Carol; Thun, Michael J (CA: a cancer journal for clinicians, 2006)
Each year, the American Cancer Society estimates the number of new cancer cases and deaths expected in the United States in the current year and compiles the most recent data on cancer incidence, mortality, and survival based on incidence data from the National Cancer Institute and mortality data from the National Center for Health Statistics. Incidence and death rates are age‐standardized to the 2000 US standard million population. A total of 1,399,790 new cancer cases and 564,830 deaths from cancer are expected in the United States in 2006. When deaths are aggregated by age, cancer has surpassed heart disease as the leading cause of death for those younger than age 85 since 1999. Delay‐adjusted cancer incidence rates stabilized in men from 1995 through 2002, but continued to increase by 0.3% per year from 1987 through 2002 in women. Between 2002 and 2003, the actual number of recorded cancer deaths decreased by 778 in men, but increased by 409 in women, resulting in a net decrease of 369, the first decrease in the total number of cancer deaths since national mortality record keeping was instituted in 1930. The death rate from all cancers combined has decreased by 1.5% per year since 1993 among men and by 0.8% per year since 1992 among women. The mortality rate has also continued to decrease for the three most common cancer sites in men (lung and bronchus, colon and rectum, and prostate) and for breast and colon and rectum cancers in women. Lung cancer mortality among women continues to increase slightly. In analyses by race and ethnicity, African American men and women have 40% and 18% higher death rates from all cancers combined than White men and women, respectively. Cancer incidence and death rates are lower in other racial and ethnic groups than in Whites and African Americans for all sites combined and for the four major cancer sites. However, these groups generally have higher rates for stomach, liver, and cervical cancers than Whites. Furthermore, minority populations are more likely to be diagnosed with advanced stage disease than are Whites. Progress in reducing the burden of suffering and death from cancer can be accelerated by applying existing cancer control knowledge across all segments of the population.